Wetland birds in Turks and Caicos Islands II: Wetland bird communities - Hilton, Geoff M; Cleeves, Tim; Murray, Tony; Hughes, Baz; Gibbs Williams, Ethlyn (Wildfowl, 2000)
Wetlands occupy a large proportion of the land area of the Turks and Caicos Islands, a U.K. Overseas Territory in the Bahamas archipelago. Furthermore, over most of the Caicos Islands these wetlands remain effectively unaltered by human activities. In the context of rapid wetland destruction and degradation in the Caribbean region, the wetland resources of Turks and Caicos are potentially of great importance for biodiversity conservation. However, very little is known about their ecology, and the bird communities they support. A survey of wetland birds in the Caicos Islands was conducted in February-April 1999. Four main wetland types were examined: lagoons, coastal saltflats, coastal mangroves and coastal beaches. The wetland bird community comprised a large number of wintering boreal-temperature waterbirds, along with characteristic resident species of Caribbean wetlands. Overall bird numbers were rather low. Cluster analysis was used to identify two broad types of lagoon habitats: shallow salinas, with exposed mud and little flooded marginal vegetation; and deeper ponds, with flooded marginal vegetation and mangrove fringes. Bird communities differed between these two lagoon types. Two globally threatened wetland species were present: West Indian Whistling-duck (Dendrocygna arborea) and Piping Plover (Charadrius melodus).